Medical school admission processes to target rural applicants: an international scoping review and mapping of Australian practices - Jordan Fox; Jessica Beattie; Janelle McGrail; Diann Eley; Lara Fuller; Wendy Hu; Catherine Keniry; Srinivas Kondalsamy Chennakesavan; Lyndal Parker-Newlyn; Katharine Reid; Lucie Walters; Matthew McGrail (BMC Medical Education)
Abstract Background Recruiting more rural origin applicants to medical school is a high priority for addressing rural workforce shortages, given evidence demonstrating they are more likely to practice rurally. Whether strategies used to select rural applicants for Australian medical schools are evidence-based is yet to be evaluated in depth. The primary aim of this study was to identify admission and selection processes utilised by Australian medical schools to target rural applicants and evaluate whether they are evidence-based against international literature. A secondary aim was to document the volume and type of publicly available information regarding admission and selection processes in Australian medical schools. Methods The study comprised two stages: (1) identified and summarised admission elements used in each Australian medical school (all pathways), how they are weighted and used to select applicants, and what strategies are used to specifically target rural origin applicants, as determined by publicly available information; and (2) conducted a scoping review of international literature to document the evidence relating to medical school admissions processes which target rural applicants and how they impact the selection of students. Results Australian medical schools employ a combination of academic performance and standardised tests to rank applicants for interview and admission; however, there was extensive variation in the specific admission elements assessed and how they were weighted and used to rank applicants. All except one medical school tailored entry requirements for rural applicants. Scoping review data revealed that on average, rural applicants achieve lower scores on academic performance metrics, although this difference was less pronounced in graduate entry compared to school leaver pathways. Overall, rural applicants achieved lower scores on standardised tests and results relating to interview performance were inconsistent across studies. Conclusions In addressing the lower mean scores from rural applicants across commonly used admission tests, our evidence confirms that modified admission processes for this applicant group are needed and are being implemented across Australian medical programs. Medical schools should continue to implement rurally-targeted admissions strategies such as adjusted entry requirements, quotas, and alternative entry pathways while setting clearly defined selection targets and evaluating the effectiveness of any strategies.